Validity and Reliability of the Fatigue Severity Scale in Patients with Chronic Kidney Disease on Dialysis in Indonesia - Rifa'i, Achmad; Satiti, Ika; Sagala, Ida; Setiabudhi, Verina (Clinical and Research Journal in Internal Medicine, 2024)
Background: Fatigue is one of the common symptoms in patients with chronic medical conditions like kidney failure that require hemodialysis. It is also associated with bad quality of life. Therefore, it is crucial to evaluate it using tools like Fatigue Severity Scale (FSS). Aim: The purpose of this study was to evaluate the reliability and validity of the translated FSS. Methods: FSS was performed on 41 chronic kidney patients undergoing dialysis. The FSS used in the study was translated from English to Bahasa Indonesia by the team. The questionnaire was assessed for its reliability and validity using Cronbach’s Alpha (CA) and Pearson Validity Test, respectively. Reliability for each item was also evaluated using the corrected item-total correlation. The scale is reliable if its CA value >0.6 and valid if the r-value is higher than the expected r on Pearson's table. Results: The scale was perceived as reliable based on the CA values from both respondent groups: 0.968 for HD and 0.952 for the CAPD group. All nine items were also deemed reliable based on the corrected item-total correlation score. Based on both r and Sig values, the translated FSS was valid for all groups: r>0.433 for HD, r>0.444 for CAPD, and Sig value <0.05. Conclusion: The translated FSS is valid and reliable, hinting at its ability to be utilized in assessing fatigue in chronic kidney patients on dialysis